Menelisik Komunikasi Restoratif Pada Pemaknaan Gender Perempuan Dalam Kelompok Jurnalis Televisi di Era Digital - Khairina, Nadhilah; M, Mujahiddin (Universitas Muhammadiyah Sumatera Utara, 2025)
The issue of gender interpretation in the television media industry in the digital era affects the experiences and interpretations of female journalists' identities. Restorative communication is an approach to resolving conflicts and building relationships carried out by companies to provide support to female television journalists. This study aims to analyze the role of restorative communication in the interpretation of female gender in journalist groups in the digital era. This study uses a qualitative approach, with a qualitative descriptive research type. Data collected through observation results, structured interviews with 5 (five) female journalists and 1 (one) news team leader who work from various different television stations and documentation. The results of the study show that the interpretation of gender identity by female television journalists is very diverse, influenced by individual experiences in the work environment, and social interactions. Female journalists still face challenges in the form of stereotypes, discrimination and gender-based violence, both in physical and digital spaces. However, gender identity is also understood as asocial capital that can strengthen the work approach of female journalists, especially in situations that require empathy and sensitivity. Restorative communication from the company in the form of a safe reporting mechanism, legal support, professional guidance and provision of adequate work facilities, provides a positive correlation in empowering female journalists. However, challenges related to gender bias and patriarchal culture are still felt, so the effectiveness of restorative communication is highly dependent on consistent implementation and an open work culture. It is concluded that restorative communication plays an important role in creating a fair work environment and providing a sense of security and support for female journalists